Causes of acquired methemoglobinemia – A retrospective study at a large academic hospital - Alex Belzer; Matthew D. Krasowski (Toxicology Reports, 2024)
Methemoglobinemia is a potentially life-threatening condition caused by the formation of methemoglobin, a form of hemoglobin that cannot bind oxygen. While there are some rare congenital causes of methemoglobinemia, most cases are acquired from the effects of specific drugs or environmental exposures. In this retrospective study, we analyzed a large data set of whole blood samples analyzed for methemoglobin at an academic medical center in Midwestern United States that provides both pediatric and adult services. For a 14 year timeframe (May 2009- June 2023), we performed detailed chart analysis of all patients with a methemoglobin concentration of 3.1 % or higher. For an earlier 13 year timeframe (January 1996-April 2009), we performed chart review for all patients with a methemoglobin concentration of 10.0 % or higher. For the 2009–2023 data, dapsone was the most frequent cause of methemoglobinemia (methemoglobin 3.1 % or higher) in both pediatric (73.3 %, 115 clinical encounters, 105 unique patients) and adult (65.3 %, 195 clinical encounters, 190 unique patients) populations. Inhaled nitric oxide as medical therapy was the next most frequent cause in both pediatric (18.1 %) and adult (13.2 %) populations. Causes associated with two or more unique episodes with methemoglobin concentrations of 10.0 % and higher included the following: dapsone (n = 40 episodes), benzocaine (n = 10), recreational use of amyl or isobutyl nitrite (n = 3), suicide attempt with sodium nitrite (n = 3 with 1 fatality; all 3 cases within last 3 years), food contaminated with nitrates (n = 2), and sepsis (n = 2). A total of 18 patients received treatment with methylene blue including 5 cases associated with benzocaine and all of the cases associated with amyl nitrite, isobutyl nitrite, sodium nitrite, and contaminated food. Only 3 patients with dapsone-associated methemoglobinemia received methylene blue, reflecting primary management by dose reduction or discontinuation of drug. Overall, our data reinforce previous studies showing dapsone, inhaled nitric oxide, and nitrites as common agents causing methemoglobinemia in a patient population seen at a medical center. Our data also are consistent with recent epidemiology trends showing increase in suicide attempts using sodium nitrite.